Challenges for meeting the global food and nutrient needs in the new millennium - Khush, Gurdev S. (Cambridge University Press, 2001)
Major advances have occurred in food production during the last 30 years as a result of the adoption of ‘green revolution’ technology. The price of rice and wheat is 40 % lower than it was in the 1950s. This lower price has helped the poorer sections of society, who spend 50–60 % of their income on food. The proportion of the population in the developing world that is malnourished fell from 46·5 % in the early 1960s to 31 % in 1995. However, there are still 1·3 billion of the population who go to bed hungry every day. Deficiencies of micronutrients such as Fe, Zn and vitamin A affect millions of the population in the developing world. The world population is increasing at the rate of 1·4 %, or an increase of eighty million per year. It is estimated that we will have to produce 50 % more food grains by 2025. Various strategies for meeting this challenge exist, including the development of cereal varieties with a higher yield potential and yield stability, and farmer-friendly public policies. In order to tackle hidden hunger, efforts are underway to develop crop varieties with higher concentrations of Fe and Zn. Recently, a breakthrough has occurred in the introduction of the genes for the pathway leading to the biosynthesis of β-carotene, a precursor of vitamin A, in rice. Various conventional approaches and modern tools of biotechnology are being employed in the development of crop varieties with higher yields and higher levels of micronutrients.